Resection of rectal cancer resembling submucosal tumor that was preoperatively diagnosed with endoscopic ultrasound-guided biopsy - Akimitsu Tanio; Hiroaki Saito; Keigo Ashida; Shouichi Urushibara; Manabu Yamamoto; Naruo Tokuyasu; Teruhisa Sakamoto; Soichiro Honjo; Yoshihiko Maeta; Yoshiyuki Fujiwara (Surgical Case Reports)
Abstract Background Colorectal cancer (CRC) resembling submucosal tumor (SMT; CRC/SMT) is very rare. Because its biopsy is challenging, accurate preoperative diagnosis is also very rare. Case presentation A 55-year-old woman with a high serum carcinoembryonic antigen level underwent a computed tomography colonoscopy, which showed extrinsic rectum compression. A coronal magnetic resonance image showed a 4-cm low-intensity tumor between her rectum and sacrum. Endoscopic ultrasound (EUS) showed a 30-mm low-echoic lesion originating from the rectum. Pathological examination of specimen obtained with EUS-guided fine-needle aspiration biopsy (EUS-FNAB) revealed adenocarcinoma. Immunohistochemical staining showed the tumor to be positive for both CK20 and CDX2 and negative for CK7, indicating that it was a rectal cancer. We performed a laparoscopy-assisted low-anterior resection with dissection of the regional lymph nodes after eight chemotherapy cycles. Macroscopically, tumor was completely covered by normal rectal mucosa, but showed a 2-mm bulge on the mucosa. Histological examination revealed a moderately differentiated adenocarcinoma, mainly located at the subserosal layer and severely invaded to lymphatic and blood vessels. The mucosal layer was not exposed to the cancer components, and her postoperative course was uneventful. Conclusion EUS-FNAB was useful in preoperative accurate diagnosis of this very rare tumor. We also review the literature and discuss CRC/SMT.